ANALYSIS OF BRAND STORYTELLING IN SKINTIFIC’S SHORT-FORM VIDEO CONTENT - Luthfiyyah, Atsarina; Aryono, Aryono; Syahrul, Syahrul; Karomah, Qori (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
This study analyzes the brand storytelling of Skintific's short-form video content and evaluates the effectiveness of influencers in promoting skincare products on Instagram, targeting the millennial and Gen Z demographic in Indonesia. The Indonesian skincare industry is experiencing significant growth, driven by a shift in consumer preferences toward skincare as a primary need, and social media's increasing influence has transformed traditional marketing. Skintific has capitalized on this trend, becoming a top brand on major e-commerce platforms. This research uses a qualitative approach with a content analysis method to identify patterns and themes in Skintific's short videos. The study's sample includes Skintific videos uploaded to TikTok and Instagram Reels between June and July 2025, selected based on their popularity and engagement. The findings are expected to provide valuable insights for business owners and serve as a reference for future research on social media marketing in the beauty industry.